2021
DOI: 10.46481/jnsps.2021.174
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Dynamics and thermodynamic Responses of XNbSn Half-Heusler Semiconductors: A First-Principles Approach

Abstract: In this work, we have evaluated how CoNbSn, IrNbSn, and RhNbSn half Heusler alloys respond to temperature change and the accompanying lattice vibrations as a cubic crystal. There are reports in the literature for CoNbSn with which we compared our result; there are, however, no reports for the other two alloys except for their Debye temperature obtained via machine learning, and our results compare well. Considering that results in the literature for IrNbSn and RhNbSn are scanty, we first computed the alloys' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…There are several experimental and computational studies reported in publications on half-Heusler alloys [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Nevertheless, the search for viable half-Heusler semiconductors with suitable properties for specific applications is still needed because some of the already discovered materials have limitations that hinder their suitability for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…There are several experimental and computational studies reported in publications on half-Heusler alloys [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Nevertheless, the search for viable half-Heusler semiconductors with suitable properties for specific applications is still needed because some of the already discovered materials have limitations that hinder their suitability for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…HH-A (Å) 5.97 5.90 [112], 5.91 [121], 5.95 [53,54,60,62,122] FH-A (Å) 6.17 6.18 [123] 6.15 [124][125][126] Ta alloys HH-A (Å) 5.96 5.97 [61], 5.89 [118],…”
Section: Nb Alloysmentioning
confidence: 99%